Microsoft: instilling a growth mindset. Issue 3 (3rd December 2018) - IBARRA, HERMINIA; RATTAN, ANEETA
Abstract : When Satya Nadella became CEO of Microsoft in February 2014, the company seemed in danger of fading into irrelevance. Now its share price is at an all‐time high. How did he do it? ByHerminia Ibarra andAneeta Rattan